Pengembangan Modul Biologi Berbasis Problem Based Learning (PBL) Untuk Meningkatkan Kemampuan Pemecahan Masalah Pada Materi Pemanasan Global - Titin Sri Suhartina (UNIVERSITAS HAMZANWADI, 2025)
based module in improving problem-solving skills. (2) To determine the effectiveness of the Biology module based on Problem Based Learning (PBL) in improving problem-solving skills. This development research uses the Borg and Gall development model which is carried out through 7 development stages, namely: 1. Preliminary information collection, 2. Planning, 3. Initial product development, 4. Small-scale trial, 5. Product revision, 6. Limited-scale trial, and 7. Product revision. The trial subjects in this study were material experts, biology teachers, design experts, 16 students for the small-scale trial, and 41 students for the large-scale trial at SMP N 2 Suela. The data collection technique used was questionnaires and the data were analyzed using quantitative descriptive analysis techniques. Based on the results of data analysis and discussion, it can be concluded that the Biology module product based on Problem Based Learning (PBL) to improve problem-solving skills is very valid and effective to be used during the learning process. This validity can be seen material experts I 82,6% and II 88,9%, from design experts obtained 87.4%, the practicality base on student responses was 2,75 with an effective category. The N-Gain acquisition of 0.61 is included in the effective category. Meanwhile, the control class obtained an N-Gain score of 0.50, which is included in the less effective category. The control class had lower test scores compared to the experimental class because the method or model used in the experimental class could improve students’ problem-solving skills. Keywords: Biology Module, Borg and Gall, Problem Based Learning (PBL), Problem-Solving Skills, Global Warming.